Valuing Private Equity Investments Strip by Strip - GUPTA, ARPIT; VAN NIEUWERBURGH, STIJN (Journal of Finance, 2021)
ABSTRACT We propose a new valuation method for private equity (PE) investments. It constructs a replicating portfolio using cash flows on listed equity and fixed‐income instruments (strips). It then values the strips using an asset pricing model that captures the risk in the cross‐section of bonds and equity factors. The method delivers a risk‐adjusted profit on each PE investment and a time series for the expected return on each fund category. We find negative risk‐adjusted profits for the average PE fund, with substantial heterogeneity and some persistence in the performance. Expected returns and risk‐adjusted profit decline in the later part of the sample.